Potenciais problemas relacionados à utilização de medicamentos para doenças cardiovasculares e diabetes mellitus em um município de Minas Gerais. - Flávia Cristina Moura Gualberto (2020)
Cardiovascular diseases (CVD) and diabetes mellitus (DM) are chronic diseases with a high prevalence that stand out among the others. Several factors contribute to their lack of control, especially those related to pharmacotherapy, which is continuous and usually complex, often leading to problems related to the use of medicines (PRM). Thus, this study aimed to identify potential PRM for the treatment of CVD and DM, as well as the factors associated with them, in individuals attended by the Unified Health System in the municipality of Congonhas, Minas Gerais. This is a cross-sectional study in which individuals were included for whom medication was dispensed in SUS in April 2019. Potential PRMs were identified based on the drugs dispensed or not dispensed and the presence of self-reported diseases (hypertension arterial hypertension - SAH; DM; or history of acute myocardial infarction - AMI). For the classification of these potential PRMs, the Pharmacotherapy Workup method was used. Logistic regression analyzes were performed to verify factors associated with the identification of at least one potential PRM. The results showed that 25% of the population had at least one potential PRM, and 1,914 potential PRMs in total were identified. The most frequent types were: non-dispensing of antihypertensive drugs for patients with self-reported SAH (n = 727); and not dispensing an angiotensin-converting enzyme inhibitor or angiotensin II receptor antagonist for patients with simultaneous self-reporting of SAH and DM (n = 398). In the multivariate model, the age group was the only variable that was shown to be positively and statistically significantly associated with the identification of at least one potential PRM (55 to 64 years - RC = 3.93; 95% CI = 3.28- 4.71; 65 years or older - RC = 8.34; 95% CI = 7.01-9.91). The present study not only allows us to trace the profile of medication use by SUS users and patients with chronic non-communicable diseases, but also supports the planning of clinical qualification services for pharmacotherapy aimed at this population, which should prioritize older individuals.